Navigating IT Careers in the Age of AI : Human Skills in an Automated Future - Rajesh Kamisetty, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article investigates the current state of AI (Artificial Intelligence), its market, and the potential impacts of AI on future jobs. The AI revolution is not only transforming the labour market across the world but also augmenting business processes and procedures in various areas. We explore the evolving relationship between human workers and AI systems in IT by analysing current trends, industry reports, and expert predictions. Nature and Extent of jobs that are likely to be affected by Automation are also a part of the study. The article offers insights into the ever-changing nature of IT roles, identifies critical skills for future success, and presents recommendations for professionals seeking to thrive in an AI-augmented work environment.
Keywords: Artificial Intelligence; Labour Market; Automation; Productivity; Information Technology